1984
DOI: 10.1113/jphysiol.1984.sp015116
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from the use of vibration that the human long‐latency stretch reflex depends upon spindle secondary afferents.

Abstract: SUMMARY1. The electromyographic activity of flexor pollicis longus has been recorded in normal human subjects on moving the tip of the thumb with the proximal phalanx clamped. Ramp and hold displacements (stretches) were compared with highfrequency sinusoidal movement (vibration). The subject exerted a constant flexor force between stimuli and made no voluntary response to them.2. On stretching the muscle by forcibly extending the thumb at various constant velocities the usual combination of short-latency (ca.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
4

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(114 citation statements)
references
References 42 publications
6
104
4
Order By: Relevance
“…This is consistent with past suggestions that the long-latency response is caused by the reactivation of primary spindle afferents following their synchronization during the short-latency reflex and subsequent refractory period (Schuurmans et al 2009). Alternatively, it may be that the load-dependent component of long-latency activity is mediated by slower secondary muscle afferents that yield a distinct phasic burst of activation at a longer latency (Grey et al 2001;Matthews 1984). Although our present results cannot distinguish between these possibilities, future experiments could focus directly on the load-dependent component when testing between these hypotheses.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This is consistent with past suggestions that the long-latency response is caused by the reactivation of primary spindle afferents following their synchronization during the short-latency reflex and subsequent refractory period (Schuurmans et al 2009). Alternatively, it may be that the load-dependent component of long-latency activity is mediated by slower secondary muscle afferents that yield a distinct phasic burst of activation at a longer latency (Grey et al 2001;Matthews 1984). Although our present results cannot distinguish between these possibilities, future experiments could focus directly on the load-dependent component when testing between these hypotheses.…”
Section: Discussionmentioning
confidence: 64%
“…For example, many studies have established that the long-latency reflex includes contributions from multiple neural pathways at various levels of the neuraxis (Gomi and Osu 1998;Kimura et al 2006;Kurtzer et al 2010;Lewis et al 2004;Lourenco et al 2006;Matthews and Miles 1988;Shemmell et al 2009), including the spinal cord (Cody et al 1986;Eklund et al 1982;Ghez and Shinoda 1978;Matthews 1984;Miller and Brooks 1981;Schuurmans et al 2009;Tracey et al 1980) and cerebral cortex (Capaday et al 1991;Cheney and Fetz 1984;Evarts 1973;MacKinnon et al 2000;Marsden et al 1977a;Matthews et al 1990;Phillips 1969). It is largely unknown, however, whether these separate neural contributors endow the long-latency reflex with unique functional capabilities (Kimura et al 2006;Matthews 2006;Shemmell et al 2009).…”
mentioning
confidence: 99%
“…However, it is also known (Rothwell et al 1986) that use of randomized intervals, which were employed in the present study, greatly reduces the habituation of the M2 response seen with fixed intervals. Furthermore, it has recently been shown that muscle stretch reflexes in HD, rather than showing more rapid habituation, actually demonstrate impaired habituation of the M2 component (Abbruzzese et al 1990 (Matthews, 1989) are contradictory to results supporting a role of secondary muscle afferents in the genesis of the M2 response which were obtained from more proximal arm muscles (Matthews, 1984). Given the differences in reflex behaviour between various muscles demonstrated in the present study, it would seem safe to infer that conflicting evidence is truly contradictory only when the relevant studies concern the same muscle.…”
Section: Discussionmentioning
confidence: 81%
“…In recent years, however, in the face of accumulating evidence that M2 responses could survive after transection of the suggested transcortical reflex loops (Ghez & Shinoda, 1978;Miller & Brook, 1981), additional explanations of the M2 mechanism have been put forward. The more significant of these are (i) that the M2 response is mediated by slower conducting afferents, specifically muscle spindle secondary endings (Matthews, 1984) or cutaneous afferents (Darton, Lippold, Shahani & Shahani, 1985); (ii) segmentation of the I a afferent volley by mechanical oscillations in the stretched muscle, the 'resonance' hypothesis (Eklund, Hagbarth, Hiigglund & Wallin, 1982 a,b); (iii) transmission of I a afferent input over polysynaptic spinal pathways (Hultborn & Wigstrdm, 1980). All of these alternative theories have received partisan support and attracted fierce criticism, but it is noticeable that the most vocal contributors to the debate have been intent on pushing through one explanation to the exclusion of all others.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical analysis of changes in firing probability was confined to the first 10 ms after the onset of monosynaptic la excitation to avoid contamination by the long-latency M2 response (see Marsden, Rothwell & Day, 1983;Matthews, 1984). Within each I ms bin a X2 test was used to determine the extent to which the distribution of firing probability after stimulation differed from that in the control situation.…”
Section: Methodsmentioning
confidence: 99%